2016
DOI: 10.1016/j.aninu.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Nano zinc, an alternative to conventional zinc as animal feed supplement: A review

Abstract: The uniqueness of Zn is that, it is the second most abundant trace element in the animal body but can't be stored in the body, thus regular dietary intake is required. Zinc oxide (ZnO) nanoparticles (NP) particles are being extensively used in paints, skin lotions pigments, food, electronics appliances, biological and pharmaceutical applications and many more. Zinc oxide nanoparticles are the specially prepared mineral salt having particle size of 1 to 100 nm. It promotes growth can act as antibacterial agent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
176
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(187 citation statements)
references
References 60 publications
4
176
1
6
Order By: Relevance
“…Earlier studies did not report any adverse effect of in ovo Zn administration on developing chicken embryo (Tako et al., ; Goel et al., ; Yair, Shahar, & Uni, ; Oliveira et al., ). The toxicity effect of zinc may be related with its bioavailability, and nano zinc is more bio‐available than organic or inorganic zinc (Swain, Rao, Rajendran, Dominic, & Selvaraju, ; Star, van der Klis, Rapp, & Ward, ). Among inorganic forms, the bioavailability of Zn in feed grade ZnO is 40%–80% relative to that of ZnSO4 (Sandoval, Henry, Ammerman, Miles, & Littell, ; Edwards & Baker, ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies did not report any adverse effect of in ovo Zn administration on developing chicken embryo (Tako et al., ; Goel et al., ; Yair, Shahar, & Uni, ; Oliveira et al., ). The toxicity effect of zinc may be related with its bioavailability, and nano zinc is more bio‐available than organic or inorganic zinc (Swain, Rao, Rajendran, Dominic, & Selvaraju, ; Star, van der Klis, Rapp, & Ward, ). Among inorganic forms, the bioavailability of Zn in feed grade ZnO is 40%–80% relative to that of ZnSO4 (Sandoval, Henry, Ammerman, Miles, & Littell, ; Edwards & Baker, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also been used as a novel tool in the fields of biotechnology, biology (molecular and cellular), physiology, mineral nutrition, pharmacology, and reproduction, etc. in both human and animal models [12]. Minerals play a vital role in the nutrition of animal production system.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that nano‐formulated Zn, like nano ZnO, promotes growth; a dose‐dependent effect of ZnO NPs was positively correlated with the growth performance and the positive immunological responses of livestock and poultry (Sahoo, Swain, & Mishra, ; Yang & Sun, ). A recent review summarized the beneficial effects of nano ZnO and its promising application as a mineral supplement to the human and livestock diet (Swain, Rao, Rajendran, Dominic, & Selvaraju, ).…”
Section: Introductionmentioning
confidence: 99%